The Irony of Contemporary Loneliness: Confirmation, Disconfirmation, and Symbolic Solace within Ubiquitous Digital Connection - Dowd, John (New Explorations)

(untitled) (New Explorations Association, 2023)
This article explores the relationship between digital environments and adverse mental health effects. I begin by operationalizing key terms including social media and loneliness, before moving to relevant literature on social media use and mental health. Next, I unpack R.D. Laing’s notion of confirmation and disconfirmation, which serves as a backdrop for thinking through online social interaction. Finally, putting Burke in conversation with Laing, I discuss the role that embodiment plays in social presence and argue that experiences of loneliness may be, contrary to claims by social media firms and techno-enthusiasts, heavily influenced by the inevitable disconfirmation that occurs in digitally mediated communication environments.